Robotic Pelvic Exenteration for Gynecologic Malignancies, Anatomic Landmarks, and Surgical Steps: A Systematic Review - Cianci, Stefano; Arcieri, Martina; Vizzielli, Giuseppe; Martinelli, Canio; Granese, Roberta; La Verde, Marco; Fagotti, Anna; Fanfani, Francesco; Scambia, Giovanni; Ercoli, Alfredo (Frontiers in Surgery, 2021)
Pelvic exenteration represents the last resort procedure for patients with advanced primary or recurrent gynecological malignancy. Pelvic exenteration can be divided into different subgroup based on anatomical extension of the procedures. The growing application of the minimally invasive surgical approach unlocked new perspectives for gynecologic oncology surgery. Minimally invasive surgery may offer significant advantages in terms of perioperative outcomes. Since 2009, several Robotic Assisted Laparoscopic Pelvic Exenteration experiences have been described in literature. The advent of robotic surgery resulted in a new spur to the worldwide spread of minimally invasive pelvic exenteration. We present a review of the literature on robotic-assisted pelvic exenteration. The search was conducted using electronic databases from inception of each database through June 2021. 13 articles including 53 patients were included in this review. Anterior exenteration was pursued in 42 patients (79.2%), 2 patients underwent posterior exenteration (3.8%), while 9 patients (17%) were subjected to total exenteration. The most common urinary reconstruction was non-continent urinary diversion (90.2%). Among the 11 women who underwent to total or posterior exenteration, 8 (72.7%) received a terminal colostomy. Conversion to laparotomy was required in two cases due to intraoperative vascular injury. Complications’ report was available for 51 patients. Fifteen Dindo Grade 2 complications occurred in 11 patients (21.6%), and 14 grade 3 complications were registered in 13 patients (25.5%). Only grade 4 complications were reported (2%). In 88% of women, the resection margins were negative. Pelvic exenteration represents a salvage procedure in patients with recurrent or persistent gynecological cancers often after radiotherapy. A careful patient selection remains the milestone of such a mutilating surgery. The introduction of the minimally invasive approach has led to advantages in terms of perioperative outcomes compared to classic open surgery. This review shows the feasibility of robotic pelvic exenteration. An important step forward should be to investigate the potential equivalence between robotic approaches and the laparotomic one, in terms of long-term oncological outcomes.